2017
DOI: 10.1111/joa.12760
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative analysis of hepatic macro‐ and microvascular alterations during cirrhogenesis in the rat

Abstract: Cirrhosis represents the end-stage of any persistent chronically active liver disease. It is characterized by the complete replacement of normal liver tissue by fibrosis, regenerative nodules, and complete fibrotic vascularized septa. The resulting angioarchitectural distortion contributes to an increasing intrahepatic vascular resistance, impeding liver perfusion and leading to portal hypertension. To date, knowledge on the dynamically evolving pathological changes of the hepatic vasculature during cirrhogene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 38 publications
2
27
1
Order By: Relevance
“…Patients with chronic liver disease usually have vascular dysfunction, especially angiogenesis, microvascular derangements and microcirculatory dysfunction [26,27]. Cirrhosis causes numerous microscopic vessel aberrations, and these vessels may become entangled with each other, resulting in sharp bends, anomalous branching patterns, abnormal branching angles and tortuosity [28]. McAvoy et al [29] demonstrated that patients with cirrhosis had selective regional increases in blood flow in the splanchnic and hepatic circulations but diminished flow in the peripheral limbs.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with chronic liver disease usually have vascular dysfunction, especially angiogenesis, microvascular derangements and microcirculatory dysfunction [26,27]. Cirrhosis causes numerous microscopic vessel aberrations, and these vessels may become entangled with each other, resulting in sharp bends, anomalous branching patterns, abnormal branching angles and tortuosity [28]. McAvoy et al [29] demonstrated that patients with cirrhosis had selective regional increases in blood flow in the splanchnic and hepatic circulations but diminished flow in the peripheral limbs.…”
Section: Discussionmentioning
confidence: 99%
“…different in contrast or colour), it is highly recommended to perform the casting simultaneously. When this cannot be achieved for logistic reasons, sequential casting can also be considered, but it is then imperative that the hepatic arterial system is filled first (Peeters et al, ). Not only can the engorgement of the portal vein with casting medium hamper the swift filling of the much smaller hepatic arterial system, in some animals such as rodents, pre‐sinusoidal one‐directional shunting vessels that are able to shift content from the arterial system to the venous system are present in the liver (Kline et al, ).…”
Section: Principles and Technique Of Corrosion Castingmentioning
confidence: 99%
“…Only when the portal vein is subsequently injected with uncontrasted resin, the shunted, contrasted resin is pushed further towards the liver sinusoids and hepatic veins, where a mixed (attenuated) contrast is normally expected. As the shunts work unidirectionally, uncontrasted resin cannot enter the hepatic arterial system prematurely (Kline et al, ; Peeters et al, ).…”
Section: Principles and Technique Of Corrosion Castingmentioning
confidence: 99%
“…During the morphological analysis, two portosystemic shunts were detected in one of the cirrhotic rats (cirrhosis 2) (illustrated in [22]), shunting blood directly from the portal trunk into the caudal vena cava. In addition, previous research documented that blood flow through the splenorenal shunt was multiplied by 3.5 in the case of TAA cirrhotic rats [15].…”
Section: ) Circulatory Disordersmentioning
confidence: 99%
“…To gather data across the entire length scale, ranging from the major blood vessels down to the smallest liverspecific capillaries (sinusoids), exponential trend lines were fitted to the geometrical attributes as a function of the generation number using a lobe-specific fitting algorithm (previously described in [16]). The total number of generations for each PV and HV lobar vascular tree was estimated by extrapolating the radius until reaching mean values representing sinusoids (reported in [22]). For 0, 6, 12, and 18-weeks intoxications, mean sinusoidal radii were measured to be 4.35 ± 0.22 µm, 4.29 ± 0.33 µm, 3.87 ± 0.38 µm, and 3.90 ± 0.45 µm, respectively.…”
Section: ) Data Analysismentioning
confidence: 99%